The severity of God religion and philosophy reconceived - Moser, Paul K., 1957- (Cambridge : Cambridge University Press, 2013)
"This book explores the role of divine severity in the character and wisdom of God, and the flux and difficulties of human life in relation to divine salvation. Much has been written on problems of evil, but the matter of divine severity has received relatively little attention. Paul K. Moser discusses the function of philosophy, evidence and miracles in approaching God. He argues that if God's aim is to extend without coercion His lasting life to humans, then commitment to that goal could manifest itself in making human life severe, for the sake of encouraging humans to enter into that cooperative good life. In this scenario, divine agapé is conferred as free gift, but the human reception of it includes stress and struggle in the face of conflicting powers and priorities. Moser's work will be of great interest to students of the philosophy of religion, and theology"--
Machine generated contents note: Preface; Introduction; 1. Severity and God; 2. Severity and flux; 3. Severity and evidence; 4. Severity and salvation; 5. Severity and philosophy; References; Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: God (Christianity); Worship; Philosophy and religion; Philosophical theology; RELIGION / Philosophy; RELIGION / General; Electronic books